Radiofrequency ablation guided by cone beam computed tomography for hepatocellular carcinoma: a comparative study of clinical results with the conventional spiral computed tomography-guided procedure. Issue 8 (August 2019) - Lyu, Tianshi; Wang, Jian; Cao, Shoujin; Song, Li; Tong, Xiaoqiang; Zou, Yinghua
Objective: To compare the outcomes of cone beam computed tomography (CBCT)-guided radiofrequency ablation (RFA) for hepatocellular carcinoma (HCC) with those of traditional spiral computed tomography (s-CT)-guided RFA. Methods: This retrospective study analysed data from patients with HCC that underwent RFA guided by either CBCT or s-CT. A number of preoperative and postoperative characteristics, including operation time, ablation time, radiation dose and hospital stay were recorded for all patients. The incidence of intraoperative and postoperative complications was recorded. The therapeutic effect was evaluated at 1, 3 and 6 months after RFA. Results: A total of 47 patients with HCC (12 females and 35 males) underwent successful RFA: 21 underwent CBCT-guided RFA and 26 underwent s-CT-guided RFA. Except for one case of pneumothorax in the s-CT group, no serious complications occurred. The objective response rate and disease control rate at 1, 3 and 6 months after RFA showed no significant differences between the two groups. Throughout the 6-month follow-up period, the complete ablation rate was 19 of 21 patients (90.5%) in the CBCT group and 19 of 26 patients (73.1%) in the s-CT group. Conclusions: CBCT was a safe and effective guiding modality for RFA in patients with HCC.